# SIMPLIFY: 4/X

## Step by Step Solution

### Rearrange:

Rearrange the equation by subtracting what is to lớn the right of the equal sign from both sides of the equation : 4/x-5-(6/x)=0## Step by step solution :

## Step 1 :

6 Simplify — xEquation at the kết thúc of step 1 : 4 6 (— - 5) - — = 0 x x

## Step 2 :

4 Simplify — xEquation at the over of step 2 : 4 6 (— - 5) - — = 0 x x## Step 3 :

Rewriting the whole as an Equivalent Fraction :3.1Subtracting a whole from a fraction Rewrite the whole as a fraction using x as the denominator :5 5 • x 5 = — = ————— 1 x Equivalent fraction : The fraction thus generated looks different but has the same value as the whole Common denominator : The equivalent fraction & the other fraction involved in the calculation nói qua the same denominator

Adding fractions that have a common denominator :3.2 Adding up the two equivalent fractions địa chỉ the two equivalent fractions which now have a common denominatorCombine the numerators together, put the sum or difference over the common denominator then reduce to lowest terms if possible:

4 - (5 • x) 4 - 5x ——————————— = —————— x x Equation at the over of step 3 : (4 - 5x) 6 ———————— - — = 0 x x

## Step 4 :

Adding fractions which have a common denominator :4.1 Adding fractions which have a common denominatorCombine the numerators together, put the sum or difference over the common denominator then reduce to lớn lowest terms if possible:(4-5x) - (6) -5x - 2 ———————————— = ——————— x x

## Step 5 :

Pulling out like terms :5.1 Pull out lượt thích factors:-5x - 2=-1•(5x + 2)Equation at the over of step 5 : -5x - 2 ——————— = 0 x

## Step 6 :

When a fraction equals zero :6.1 When a fraction equals zero ...Where a fraction equals zero, its numerator, the part which is above the fraction line, must equal zero.Now,to get rid of the denominator, Tiger multiplys both sides of the equation by the denominator.Here"s how:-5x-2 ————— • x = 0 • x x Now, on the left hand side, the x cancels out the denominator, while, on the right hand side, zero times anything is still zero.The equation now takes the shape:-5x-2=0

Solving a Single Variable Equation:6.2Solve:-5x-2 = 0Add 2 to lớn both sides of the equation:-5x = 2 Multiply both sides of the equation by (-1) : 5x = -2 Divide both sides of the equation by 5:x = -2/5 = -0.400